1989
DOI: 10.1152/ajpheart.1989.257.1.h132
|View full text |Cite
|
Sign up to set email alerts
|

Alpha 2-adrenoceptor stimulation can augment coronary vasodilation maximally induced by adenosine in dogs

Abstract: To determine whether alpha 2-adrenoceptor stimulation can augment adenosine-induced coronary vasodilation, 34 open-chest dogs were studied. When a small dose of clonidine (up to 0.24 micrograms.kg-1.min-1 ic) was administered under beta-adrenoceptor blockade, coronary blood flow [312 +/- 16 (SE) ml.100 g-1.min-1] maximally induced by intracoronary infusion of adenosine was further increased (P less than 0.05) by 66 +/- 16 ml.100 g-1.min-1, despite no significant changes in coronary perfusion pressure, myocardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 0 publications
2
7
0
Order By: Relevance
“…[59][60][61] This is consistent with the earlier studies of Nayler et al 63 They observed that phenoxybenzamine, a non-specific -adrenoceptor antagonist, blocks the vasodilatory action of adenosine in isolated rat and guinea pig hearts. [60][61][62] Furthermore, the reduction in ischemiainduced myocardial damage by administration of clonidine in coronary hypoperfusion and in coronary microembolization strongly suggests that adenosine plays an important role in the dilation of the coronary arterial bed; clonidine significantly increased coronary blood flow in both of the ischemic models without augmentation of adenosine release. 63 In summary, during ischemia, coronary blood flow is regulated by metabolic and neural mechanisms, ie, adenosine-induced coronary vasodilation and -adrenoceptormediated vasoconstriction.…”
Section: Adenosine Production In the Heartsupporting
confidence: 89%
See 2 more Smart Citations
“…[59][60][61] This is consistent with the earlier studies of Nayler et al 63 They observed that phenoxybenzamine, a non-specific -adrenoceptor antagonist, blocks the vasodilatory action of adenosine in isolated rat and guinea pig hearts. [60][61][62] Furthermore, the reduction in ischemiainduced myocardial damage by administration of clonidine in coronary hypoperfusion and in coronary microembolization strongly suggests that adenosine plays an important role in the dilation of the coronary arterial bed; clonidine significantly increased coronary blood flow in both of the ischemic models without augmentation of adenosine release. 63 In summary, during ischemia, coronary blood flow is regulated by metabolic and neural mechanisms, ie, adenosine-induced coronary vasodilation and -adrenoceptormediated vasoconstriction.…”
Section: Adenosine Production In the Heartsupporting
confidence: 89%
“…The underlying mechanism for this phenomenon may be different from that of adenosine release when -adrenoceptors are stimulated. 59 We have also found that 2-adrenergic activity modifies the vasodilatory action of adenosine (Fig 3); a low dose of the 2-adrenoceptor agonist clonidine enhances adenosineinduced coronary vasodilation, [60][61][62] and low doses of yohimbine and rauwolscine, 2-adrenoceptor antagonists, reduce the coronary flow response to either endogenous or exogenous adenosine. [59][60][61] This is consistent with the earlier studies of Nayler et al 63 They observed that phenoxybenzamine, a non-specific -adrenoceptor antagonist, blocks the vasodilatory action of adenosine in isolated rat and guinea pig hearts.…”
Section: Adenosine Production In the Heartmentioning
confidence: 75%
See 1 more Smart Citation
“…31,32 The mechanism for the adrenergic-adenosine interaction found in the present experiments is unknown. Adrenergic 3-receptor agonists have been shown to increase adenosine concentration in both coronary venous plasma33.34 and epicardial well'2 measurements.…”
Section: A-receptor-and P-receptor-blocked Experimentsmentioning
confidence: 79%
“…30 In animal models, the distribution of adrenergic receptors, in particular ␣ 2 -receptors, across the microcirculation is heterogeneous 31 and may explain enhanced vasoreactivity in response to adenosine. 32,33 Because reinnervation is heterogeneous, the minimal achievable coronary vascular resistance in innervated versus denervated beds may be different. Reinnervation differences could potentially modify regional left ventricular metabolism and subsequently regional blood flow.…”
Section: Sources Of Variability Of Cfrmentioning
confidence: 99%